Traductibilité et design : explorer les paramètres génératifs du brief - Laurent Mertz; Justine Peneau; Dorian Reunkrilerk (Appareil)
This article aims to explore what translatology can enlight on design practice. Just as translation is based on an interpretative activity of an original text, design translates a need often expressed by a third party through different media, and more specifically from the design brief. Designers must then enter, like translators, into a form of negotiation with different actors and situations. As Walter Benjamin (1968) demonstrates, in translatology this negotiation can be based on two opposite approaches: one he calls literal translation and the other translatability. The first one freezes languages and their malleable nature, unlike the second one which creates new language potential. In the case of design, the interpretive activity generally begins with the translation of a brief. This becomes the source material from which the project will take shape. We establish the hypothesis that the brief is carrying parameters leading the designers to adopt one or the other of these two approaches (literal translation or translatability). Our analysis of five briefs from different companies allows us to highlight some of these fundamental parameters such as: the influence of the circulation of versions of a brief on the design strategy, the mutual projection of postures between the actors or the gap or the alignment between each stakeholder’s horizon of expectations. These parameters therefore lead us to consider the brief as a generative apparatus as opposed to an inhibiting “dispositif”.